KONDISI SOSIAL EKONOMI NELAYAN KERAPU (FAMILI SERRANIDAE) DI PERAIRAN TELUK KOTANIA, SERAM BAGIAN BARAT, PROVINSI MALUKU - Wawo, M; Huliselan, N V; Tuapattinaja, M A; Sahetapy, D (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2017)
The coastal region of Kotania Bay located in the Western part of Seram Island is a semi-enclosed coastal area that has a unique ecosystem of mangrove ecosystems, seagrass and coral reefs that live side by side with each other. In these ecosystems there is a rich diversity of marine biological resources such as fish, molluscs, ecinoderms, crustaceans and macro-algae of economic and non-economic value. Grouper fish (Serranidae) and groups of snapper (Lutjanidae) are important economical fish that have the largest number of species in these waters. Thus, the role of coastal communities in this case grouper fisherman is very necessary in the management of grouper fish resources in the future.Therefore, this study aims to examine the socio-economic condition of grouper fishermen (Serranidae family) in the waters of Kotania Bay, West Seram, Maluku Province.Based on the results of research, the main livelihoods of people in the coast of Kotania Bay are fishermen, are in the productive age category, with a considerable level of elementary school education. The number of fishermen with <20 years' business experience is high. 55% of fishermen income> Rp. 100.000.000 and including prosperous category. Four types of traditional fishing gear are operated by fishermen in the waters of Kotania Bay to catch the economical fish, primarily grouper fish. Economical fishing areas, especially grouper fish from four fishing gear by habitat in the waters of Kotania Bay have been mapped. ABSTRAK Wilayah pesisir Teluk Kotania yang berada di Pulau Seram bagian barat merupakan wilayah pesisir semi tertutup yang memiliki keunikan ekosistem berupa ekosistem mangrove, padang lamun dan terumbu karang yang hidup saling berdampingan satu sama lainnya. Pada ekosistem tersebut terdapat keanekaragaman sumberdaya hayati laut yang kaya seperti, ikan, moluska, ekinodermata, krustasea dan makro-algae yang bernilai ekonomi dan non-ekonomi. Ikan kerapu (Serranidae) dan kelompok ikan kakap (Lutjanidae) merupakan ikan ekonomis penting yang memiliki jumlah spesies terbanyak pada perairan tersebut. Dengan demikian, peranan masyarakat pesisir dalam hal ini nelayan kerapu sangat diperlukan dalam pengelolaan sumberdaya ikan kerapu ke depan. Untuk itu, penelitian ini bertujuan untuk mengkaji kondisi sosial ekonomi nelayan kerapu (famili Serranidae) di perairan Teluk Kotania, Seram Bagian Barat, Provinsi Maluku. Berdasarkan hasil penelitian, mata pencaharian utama masyarakat di pesisir Teluk Kotania adalah nelayan, berada pada kategori umur produktif, dengan tingkat pendidikan SD yang cukup banyak. Jumlah nelayan dengan pengalaman usaha < 20 tahun tergolong tinggi. Pendapatan 55% nelayan > Rp. 100.000.000 dan termasuk kategori sejahtera. Empat jenis alat tangkap tradisional dioperasikan oleh nelayan di perairan Teluk Kotania untuk menangkap ikan ekonomis, utamanya ikan kerapu. Daerah penangkapan ikan ekonomis, terutama ikan kerapu dari empat alat tangkap menurut habitat di perairan Teluk Kotania berhasil dipetakan. Kata kunci: Sosial, Ekonomi, Nelayan kerapu, Serranidae, Teluk Kotania